Mathematical Optimization of the Combination of Radiation and Differentiation Therapies for Cancer - Bachman, Jeff W.; Hillen, Thomas (Frontiers in Oncology, 2013)
Cancer stem cells (CSC) are considered to be a major driver of cancer progression and successful therapies must control CSCs. However, CSC are often less sensitive to treatment and they might survive radiation and/or chemotherapies. In this paper we combine radiation treatment with differentiation therapy. During differentiation therapy, a differentiation promoting agent is supplied (e.g., TGF-beta) such that CSCs differentiate and become more radiosensitive. Then radiation can be used to control them. We consider three types of cancer: head and neck cancer, brain cancers (primary tumors and metastatic brain cancers), and breast cancer; and we use mathematical modeling to show that combination therapy of the above type can have a large beneficial effect for the patient; increasing treatment success and reducing side effects.